Motivational cherry picking - Tobias Regner; Gerhard Riener (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We construct a simple three person trust game with one trustor and two trustees. The trustor has the possibility to either trust both trustees or none, while the trustees make their decisions either sequentially or simultaneously, depending on the treatment. When trustees play sequentially, follower trustees who are informed about the leader's choice are significantly more selfish than in the simultaneous move treatment, independent of the leader's choice. Leaders do not behave significantly different than in the baseline treatment. Follower trustees cherry pick the motivation that materially serves them best. When the leader trustee plays selfish, they tend to conform. When the leader makes a pro-social choice, followers seem to perceive the duty as already fulfilled by the leader. While guilt works well as a motivational force in a dyadic situation, it gets alleviated easily when the situation allows a shifting of responsibility.
Keywords: D03; D71; C79; C92; 330; Team production; Trust; Choice architecture; Guilt aversion; Conformity; False consensus effect; Lab experiment; Cherry picking